2018
DOI: 10.33899/rjs.2018.163144
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric Determination of Sulfamethoxazole in Pure and in Pharmaceutical Preparations by Diazotization and Coupling Reaction

Abstract: A highly sensitive, simple and accurate spectrophotometric method has been developed for quantitative determination of sulfamethoxazole(SMX) in both pure form and pharmaceutical preparations. In this method SMX is diazotized with equimolar of sodium nitrite(NaNO 2) in acid medium of hydrochloric acid to form diazonium ion , which is reacted with 2,4,6-trihydroxybenzoic acid in alkaline medium of NaOH to form a yellow water soluble azo dye that has absorption maximum at 416 nm versus reagent blank. Beer's law i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…S ulfamethoxazole(SMZ) is a member of the sulfonamide family of antibacterials and the chemical name is 4-Amino-N-(5-methyl-3-isoxazolyl)-benzene sulfonamide [1]. It is one of many antibiotics [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S ulfamethoxazole(SMZ) is a member of the sulfonamide family of antibacterials and the chemical name is 4-Amino-N-(5-methyl-3-isoxazolyl)-benzene sulfonamide [1]. It is one of many antibiotics [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is one of many antibiotics [2]. A survey of the literature showed that different techniques have been reported for SMZ analysis, some of which include spectrophotometric methods [1], for instance, HPLC [3], electrochemical methods [4] an solid phase extraction [5]. Diazotization method is simple and inexpensive method.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the aforementioned procedures involved oxidative coupling reactions with thymol in the existence of sodium meta periodate (Salih & Mohammed, 2020), phenothiazine in the presence of potassium sulphate (K2SO4) as oxidant (Shehab & Muhammed, 2020), pyrocatechol and K2SO4 (Shihab, 2011), histidine in the presence of N-bromosuccinimide (NBS) (Zakaria, 2019), 8-hydroxyquinoline and N-(1-naphthyl) ethylenediamine (NNED) in alkaline solution (Zakaria, 2013). Others depended on the diazotization reaction of MESZ and coupling with some reagents for instance, 2,6-dihydroxytoluene (Aziz & Sultan 2019), resorcinol (Madhavi et al, 2011) and phlorogycinol (Hamdon et al, 2012). A condensation reaction was also applied to estimate MESZ via spectrophotometric methods by using reagents of salicylaldehyde (Anumolu et al, 2019) and pdimethylaminocinnamaldehyde (Sama et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These techniques are expensive and need special training. Also, spectrophotometric methods have been reported for determination of SMX using different reagents such as, vanillin [10], 2,3-dichloro-5,6-dicyano-1,4-benzoquinone, p-chloranil and picric acid [11], phenoxazine [12], 2,4,6-trihydroxybenzoic [13], 1-naphthol [14], 2-naphthol [15], Salbutamol sulphate [16], thymol [17], and Diphenylamine [18]. Some of these methods are disadvantageous, in terms of sensitivity, and require extraction or heating steps.The present study is developing a new sensitive and simple spectrophotometric method for determination of SMX in pure and dosage forms, depending on formation of a new product by the reaction of SMX with 9-chloroacridine (9-CA).…”
Section: Introductionmentioning
confidence: 99%